Underground Water Resources Management for Flooding Prevention - Sierikova, Olena; Strelnikova, Elena; Degtyariov, Kyryl (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
Technogenic factors that affect urban area flooding development, forecasts of improving groundwater level changes, and comprehensive management of urban groundwater must be taken into account and controlled. A three-dimensional mathematical model of groundwater level changes in cities has been developed, which takes into account atmospheric water infiltration, additional groundwater replenishment, transpiration, evaporation, evapotranspiration, and groundwater intake.